A Critical Review on Advancement in Analytical Strategies for the Quantification of Clinically Relevant Biological Transporters. (3rd October 2022) - Modiwala, Mustafa; Jadav, Tarang; Sahu, Amit Kumar; Tekade, Rakesh K.; Sengupta, Pinaki
Abstract: Success of a drug discovery program is highly dependent on rapid scientific advancement and periodic inclusion of sensitive and specific analytical techniques. Biological membrane transporters can significantly alter the bioavailability of a molecule in its actual site of action. Expression of transporter proteins responsible for drug transport is extremely low in the biological system. Therefore, proper scientific planning in selection of their quantitative analytical technique is essential. This article discusses critical advancement in the analytical strategies for quantification of clinically relevant biological transporters for the drugs. Article cross-talked key planning and execution strategies concerning analytical quantification of the transporters during drug discovery programs.